Acanthosis Nigricans in Children and Adolescents with Type 1 Diabetes or Obesity: The Potential Interplay Role between Insulin Resistance and Excess Weight - Valeria Calcaterra; Annalisa De Silvestri; Laura Schneider; Miriam Acunzo; Viola Vittoni; Giulia Meraviglia; Francesco Bergamaschi; Gianvincenzo Zuccotti; Chiara Mameli (MDPI AG, 2021)
Acanthosis nigricans (AN) is associated with obesity and type 2 diabetes, where insulin resistance (IR) is considered a predisposing factor. IR can also affect patients with type 1 diabetes (T1D). We evaluated the prevalence of AN in patients with T1D compared to subjects with obesity in order to define the interplay between IR and excess weight. We considered 138 pediatric patients who presented with T1D and 162 with obesity. As controls, 100 healthy normal-weight subjects were included. A physical examination with the detection of AN and biochemical assessments was performed. IR was calculated by using the homeostasis model assessment for IR in patients with obesity and the estimated glucose disposal rate in T1D. The AN prevalence was higher in T1D and obese subjects compared with controls in whom AN was not detected (p = 0.02 and p < 0.001, respectively). A greater number of AN cases were observed in subjects with obesity compared with T1D (p < 0.001). Patients with AN were older than subjects without AN (p = 0.005), and they had higher body mass index (BMI) values, waist circumference (WC), fasting triglycerides and blood pressure (all p < 0.001). Thirty-five patients with AN exhibited IR with an association between AN presence and IR in patients with obesity (p < 0.001). In T1D, there was an association between AN and being overweight/obese (p = 0.02), independently of IR. AN is a dermatological condition associated with obesity. In T1D, the presence of AN was significantly associated with overweight status or obesity but not IR. The presence of AN in the absence of IR supports the interplay role between impaired insulin signaling, IR and excess weight in the pathogenic mechanism.